THE WORLD'S ROLE OF UZBEK NATIONAL DRESSES - Alijonov Nurbek Ulug‘bek o‘g‘li; Xomidova Munisaxon Ilhomjon qizi (Journals Park Publishing, 2023)
This article is about the role of Uzbek national dresses worldwide and describes a criterion that reflects the national identity of peoples and shows ethnic characteristics among material and spiritual monuments.
Keywords: yodgorlik, milliylik, libos, atlas, adras, do‘ppi, beqasam, banoras, zar chopon.